Peptide Vectors Carry Pyrene to Cell Organelles Allowing Real‐Time Quantification of Free Radicals in Mitochondria by Time‐Resolved Fluorescence Microscopy. (4th February 2021) - Wawi, Mohamad Jamal; Bijoux, Amandine; Inguimbert, Nicolas; Mahler, Christoph; Wagner, Stephan; Marder, Todd B.; Ribou, Anne‐Cécile
Abstract: Real‐time quantification of reactive nitrogen and oxygen species (ROS) in cells is of paramount importance as they are essential for cellular functions. Their excessive formation contributes to the dysfunction of cells and organisms, ultimately leading to cell death. As ROS are mostly produced in the mitochondria, we have synthesized a fluorescent probe able to reach this organelle to detect and quantify, in real time, the variation of ROS by time‐resolved microfluorimetry. The new probes are based on the long fluorescence lifetime of pyrene butyric acid (PBA). Two PBA isomers, attached at their 1‐ or 2‐positions to a peptide vector to target mitochondria, were compared and were shown to allow the measurement of free radical species and oxygen, but not non‐radical species such as H2 O2 . Abstract : On and off ROS formation detected . Two pyrene butyric acid isomers, and their respective derivatives produced by grafting them onto a peptide vector, demonstrated outstanding real‐time quantification of intracellular and mitochondrial free radicals and oxygen. The four fluorescent probes work well inside living cells for detection by time‐resolved fluorescence spectroscopy.